INDUSTRIAL RECONVERSION OF PERUVIAN SMES: CHANGE FOR COMPETITIVENESS - Schwarz Díaz, M.G. (Nexo Revista Científica, 2017)
This research explores the main constraints of Peruvian SMEs on their way towards export potential competitiveness for international markets. The research is descriptive and explanatory, non - experimental design and qualitative approach through 114 interviews of a selection of 45 typical SMEs sampled in a non - random way of intentional type. The research shows the opinion of SME entrepreneurs on the main perceived constraints affecting the competitiveness of Peruvian SMEs and conceptually defines the needs of industrial reconversion, modernization, integration and change that are required to achieve global competitiveness.